2008
DOI: 10.2527/jas.2007-0070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium magnesium carbonate and roughage level on feedlot performance, ruminal metabolism, and site and extent of digestion in steers fed high-grain diets1,2

Abstract: ABSTRACT:A feedlot growth performance experiment and 2 metabolism experiments were conducted to evaluate dietary roughage concentration and calcium magnesium carbonate in steers fed a high-grain diet. In Exp. 1, one hundred ninety-two crossbred yearling steers (320 ± 10 kg of initial BW) were fed diets based on steam-flaked corn with 0, 0.75, or 1.5% CaMg(CO 3 ) 2 . There were no effects (P ≥ 0.13) on ADG, DMI, G:F, or total water intake due to CaMg(CO 3 ) 2 . In Exp. 2, five ruminally and duodenally fistulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
2
20
0
1
Order By: Relevance
“…6). This is expected based on earlier data reporting the successful direct prediction from NIR scans to estimate intake of DM or organic matter or digestible matter (Norris et al, 1976; Ward et al, 1982; Eckman et al, 1987; Coelho et al, 1988; Lippke and Barton, 1988; Lippke et al, 1989; Coleman et al, 1999) as well as daily animal gains (Lippke et al, 1989).…”
Section: Reassessing Nutritive Valuementioning
confidence: 73%
See 4 more Smart Citations
“…6). This is expected based on earlier data reporting the successful direct prediction from NIR scans to estimate intake of DM or organic matter or digestible matter (Norris et al, 1976; Ward et al, 1982; Eckman et al, 1987; Coelho et al, 1988; Lippke and Barton, 1988; Lippke et al, 1989; Coleman et al, 1999) as well as daily animal gains (Lippke et al, 1989).…”
Section: Reassessing Nutritive Valuementioning
confidence: 73%
“…al., 2004). In their assessment and assessment by others (Shenk and Westerhaus, 1994; Coleman et al, 1999; Coleman et al, 2004) the traditional contrived fractions of NVAL were shown to be well predicted through proper calibration using near‐infrared technology. Technology advancement, however, is little served by this approach as the same inconsistencies of the NVAL fractions, relative to predicting animal response, still remain.…”
Section: Reassessing Nutritive Valuementioning
confidence: 96%
See 3 more Smart Citations